Functional fitness benchmark values for older adults: a systematic review - Marco Cossio-Bolaños; Marco Cossio-Bolaños; Ruben Vidal-Espinoza; Ignacio Villar-Cifuentes; Luis Felipe Castelli Correia de Campos; Luis Felipe Castelli Correia de Campos; Marcela Silva Ramos de Lázari; Camilo Urra-Albornoz; Jose Sulla-Torres; Rossana Gomez-Campos; Rossana Gomez-Campos (Frontiers in Public Health, 2024)
IntroductionThe use of normative values and/or standards of functional fitness in adults is relevant to overall health and well-being. The objectives of the study were: to identify the physical tests of the senior fitness test (SFT) that have been applied since its proposal and to describe the proposed percentiles according to age, sex and country.MethodsA systematic review study was conducted in the Pubmed and Scopus databases. As eligibility criteria, we considered the period from 1999 to 2022 that presented data on SFT test used in the population over 60  years of age and that described normative values through percentiles. MeSH were used as: (1) Physical fitness, Exercise test, Senior Fitness Test, Functional fitness, Cardiorespiratory fitness, (2) older adult, aged, (3) Reference standards, standards, standards of care. Boolean operators “AND” and “OR” were included. Data extracted from the selected studies included: year of publication, country, sample age, sample size, sample sex, fitness component.Results and discussionSeven studies were identified in five countries (03 in China, 01 in Poland, 01 in Portugal, 01 in Spain and 01 in United States). The age range ranged from 60 to 103  years. The studies were conducted in both sexes. The study with the smallest sample size was by Chung et al. (China) with 944 participants and the largest number of participants was the study by Rikli and Jones in the United States with 7,183 participants. In general, no study was able to complete 100% (8 components) of the tests proposed in the SFT. Normative values were presented through percentile distribution (p10, p50 and p90) organized by age ranges. Males presented better performance in FPF tests than females in all tests. Since the first publication of the SFT until 2022, seven articles have been published in countries such as United States, China (three regional studies), Poland, Portugal and Spain. No study has published the complete battery with its eight components. The percentiles of functional fitness reflect decline with advancing age.Systematic review registrationPROSPERO (CRD42023441294: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023441294).